Advancements in mental skills training: An Introduction - Terry, P. C.; Bertollo, M.; Filho, E. (Advances in mental skills training, 2021)
Broadening the influence of sport psychology in society as a whole, by strengthening the nexus between mental skills training and daily life, represents an excellent opportunity for the profession. Sport psychologists routinely help athletes to handle pressure, to become more resilient, to enhance self-esteem, and to fulfil potential. Applying these processes to life challenges outside of sport by expanding the concept of performance to include daily functioning at work, interpersonal relationships, or leisure pursuits, sport psychologists have the capacity to influence the psychological wellbeing of a much wider spectrum of society. An inevitable future development for the sport psychology field will be to optimize strategies for utilizing the internet in the provision of effective web-based mental skills training and other psychological interventions, including online mood profiling (e.g., www.moodprofiling.com) for sport, education, business, military, or health contexts (see Lane & Terry, 2016; van Wijk, Martin, & Hans-Arendse, 2013). Furthermore, as sport psychology and mental skills training evolve into the future, it is clear that the further integration of technological advancements into the profession will occur (Schack, Bertollo, Koester, Maycock, & Essig, 2014). For example, brain technologies, such as EEG neurofeedback, are becoming progressively more portable, user-friendly, and affordable, opening up potential uses in the field that were previously impossible, such as assessing brain activity associated with optimum performance in selfpaced sports and developing multibrain (or hyperbrain) analyses and interventions (see Bertollo et al., 2020; Filho & Tenenbaum, 2019). Similarly, the ever-expanding capacity of smart devices offers a range of future applications, including remote delivery by practitioners of individualized interventions for athletes combining music, video clips, and personalized instructions. Virtual reality technology similarly offers potential for more sophis-ticated use of simulation training, allowing athletes to "practice" in venues they have not yet visited, in environmental conditions they have not yet experienced, and against competitors they have not yet faced. The field of mental skills training has come a very long way since its origins more than a century ago, but as the chapters of this book attest, it is striving to set new goals, develop new techniques, and identify new directions as it moves through the 21st century.